Caracterização da interação dos bacteriofagos T4, M13, e MS2 com células epiteliais prostáticas tumoriais (LNCaP e PC3): ativação das vias de proliferação, sobrevivência e morte celular. - Sanmukh, Swapnil Ganesh [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
O câncer de próstata (PCa) é o segundo tipo de câncer mais frequente e tem a segunda maior taxa de morbidade e mortalidade entre os homens. A cultura de células prostáticas LNCaP e PC3 tem sido utilizada para investigar possíveis alvos e vias de sinalização celular importantes para o crescimento e progressão do CaP. Trabalhos anteriores do nosso laboratório demonstraram que a presença de fibronectina no meio de cultura altera significativamente o padrão de expressão gênica dessas células. Também, bacteriófagos recentemente usados como agentes terapêuticos no tratamento de vários tipos de câncer, diretamente ou portadores de moléculas antitumorais, incluindo câncer de próstata, foram relatados. Estudos anteriores mostraram que bacteriófagos podem interagir com proteínas de membrana de células de mamíferos, incluindo integrinas que reconhecem sequências de RGD em proteínas virais, bem como fibronectina e outras moléculas da matriz extracelular. O objetivo deste projeto foi caracterizar a interação de três bacteriófagos com as duas linhagens celulares epiteliais prostáticas LNCaP e PC3. Estas duas linhas celulares foram cultivadas em seus meios de cultura, nos quais foram adicionados bacteriófagos com concentrações definidas. As células foram coletadas após 24 horas de tratamento. A expressão gênica de genes relacionados as vias integrinas ITGA5, ITGAV, ITGB1, ITGB3, ITGB5, AKT, PI3K, MAPK1, MAPK3, HSP27, HSP90, receptor de androgênio AR, STAT3, PGC1A foi analisada por qPCR. A ativação da via AKT/PI3K foi analizada também por western blotting. Celulas PC3 foram expostas aos bacteriófagos T4 e M13 e foram analisadas por microscopia de luz convencional e por microscopia de varredura. Nas células LNCaP, o bacteriófago M13 regulou negativamente genes ITGA5, ITGAV, ITGB1, ITGB3, ITGB5, MAPK1, MAPK3, HSP90, TBP, PSA e positivamente genes AKT, PI3K, HSP27, AR, STAT3, PGC1A genes; o bacteriófago MS2 regulou negativamente genes ITGA5, ITGAV, ITGB3, ITGB5, MAPK1, MAPK3, HSP90, PI3K, PSA e positivamente genes ITGB1, AKT, HSP27, AR, TBP, STAT3, PGC1A genes; o bacteriófago T4 regulou negativamente genes ITGA5, ITGB3, ITGB5, HSP27, HSP90, TBP, PGC1A, PSA e positivamente genes ITGB1, ITGAV, AKT, PI3K, AR, MAPK1, MAPK3, STAT3 genes. Já para as células PC3, os bacteriófagos M13 e T4 regularam negativamente genes HSP27, HSP90, AR e positivamente os genes ITGA5, ITGAV, ITGB3, ITGB5. Microscopicamente foi possível observar a interação dos bacteriófagos T4 e M13 com a superfície celular das células PC3 e que está interação com o bacteriófago M13 reduz a migração celular. Nossos resultados sugerem que os 3 bacteriófagos poderm alterar a expressão de genes relacionados à adesão e proliferação celular, de uma maneira célula específica e podem funcionar como nanopartículas com potencial terapêutico para o tratamento de diferentes tipos de câncer, incluindo o câncer de próstata.

Prostate cancer (PCa) is the second most frequent type of cancer and has the second highest rate of morbidity and mortality among men. The LNCaP and PC3 prostate cell culture has been used to investigate possible targets and cell signaling pathways important for the growth and progression of PCa. Previous work from our laboratory has demonstrated that the presence of fibronectin in the culture medium significantly alters the gene expression pattern of these cells. Also, bacteriophages recently used as therapeutic agents in the treatment of various types of cancer, directly or carriers of antitumor molecules, including prostate cancer, have been reported. Previous studies have shown that bacteriophages can interact with mammalian cell membrane proteins, including integrins that recognize RGD sequences in viral proteins, as well as fibronectin and other extracellular matrix molecules. The objective of this project was to characterize the interaction of three bacteriophages (T4, M13, and MS2) with the two prostatic epithelial cell lines LNCaP and PC3. These two cell lines were cultured in their culture media, in which bacteriophages with defined concentrations were added. Cells were collected after 24 hours of treatment. The gene expression of genes related to the integrin pathways ITGA5, ITGAV, ITGB1, ITGB3, ITGB5, AKT, PI3K, MAPK1, MAPK3, HSP27, HSP90, androgen receptor AR, STAT3, PGC1A was analyzed by qPCR. Activation of the AKT / PI3K pathway was also analyzed by western blotting. PC3 cells were exposed to T4 and M13 bacteriophages and analyzed by standard light microscopy and scanning microscopy. In the LNCaP cells, the bacteriophage M13 regulated negatively genes ITGA5, ITGAV, ITGB1, ITGB3, ITGB5, MAPK1, MAPK3, HSP90, TBP, PSA and positively AKT genes, PI3K, HSP27, AR, STAT3, PGC1A genes; the bacteriophage MS2 negatively regulated genes ITGA5, ITGAV, ITGB3, MAPK1, MAPK3, 18 ABSTRACT Sanmukh, SG. Tese de Doutorado – Laboratório de Matriz Extracelular / BGA / UNESP / Botucatu – SP. HSP90, PI3K, PSA and positively genes ITGB1, AKT, HSP27, AR, TBP, STAT3, PGC1A genes; the bacteriophage T4 regulated negatively genes ITGA5, ITGB3, ITGB5, HSP27, HSP90, TBP, PGC1A, PSA and positively genes ITGB1, ITGAV, AKT, PI3K, AR, MAPK1, MAPK3, STAT3 genes. As for PC3 cells, M13 and T4 bacteriophages negatively regulated HSP27, HSP90, and AR genes and positively regulated the ITGA5, ITGAV, ITGB3, ITGB5 genes. Microscopically it was possible to observe the interaction of T4 and M13 bacteriophages with the cell surface of PC3 cells and that interaction with bacteriophage M13 reduces cell migration. Our results suggest that the 3 bacteriophages can alter the expression of genes related to cell adhesion and proliferation in a cell specific manner and may function as nanoparticles with therapeutic potential for the treatment of different types of cancer, including prostate cancer.
Characterization of the interaction of T4, M13, and MS2 bacteriophage with tumoral prostatic epithelial cells (LNCaP and PC3): activation of proliferation pathways, survival and cell death.
Keywords: Câncer; próstata; bacteriófago; expressão gênica; integrinas; cultura célula; prostate; gene expression; bacteriophage; integrins; cell culture